2016
DOI: 10.1002/jcla.22074
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of galectin-3, serum creatinine, and cystatin C in chronic kidney diseases

Abstract: Our study verified Gal-3, CysC and SCr were negatively related to eGFR. Besides, it is suggested that Gal-3 can be used as an indicating factor in the diagnosis of CKD; the joint analysis of Gal-3, CysC and SCr for CKD may distinctly improve diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Gal-3 is a well-established biomarker for cardiac fibrosis, ventricular dysfunction, and poor prognosis in heart failure [ 21 23 ]. In addition, Gal-3 has demonstrated diagnostic and prognostic value in diseases of the kidney [ 9 , 11 , 18 ]. Drechsler et al found a positive association between elevated levels of Gal-3 and adverse outcomes in patients with preexisting renal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gal-3 is a well-established biomarker for cardiac fibrosis, ventricular dysfunction, and poor prognosis in heart failure [ 21 23 ]. In addition, Gal-3 has demonstrated diagnostic and prognostic value in diseases of the kidney [ 9 , 11 , 18 ]. Drechsler et al found a positive association between elevated levels of Gal-3 and adverse outcomes in patients with preexisting renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, Gal-3 is acutely up-regulated in the kidneys in response to ischemic and toxic injury and is associated with renal fibrosis [ 14 17 ]. In humans, elevated levels of circulating Gal-3 have been found to be associated with increased risk of incident chronic kidney disease (CKD) and loss of kidney function over time [ 11 , 18 ]. Gal-3 therefore can be considered a marker of both acute and chronic inflammatory processes in the kidneys, even in the absence of traditional clinical markers of renal injury.…”
Section: Introductionmentioning
confidence: 99%
“…Current practices utilize two categories of biomarkers for CKD, those that estimate GFR and those that indicate damage to a specific renal function (albuminuria). Similarly, the search for new biomarkers has two directions, indicators of GFR which are routinely assayed in the serum[ 211 - 219 ] and indicators of specific types of kidney injury which are assayed in the urine or serum[ 220 - 227 ].…”
Section: Future Developmentsmentioning
confidence: 99%
“…Galectin‐3 is an α‐galactoside‐binding lectin that has been shown to mediate cell‐to‐cell and cell‐to‐extracellular matrix interactions and act as a novel chemoattractant for monocytes and macrophages . Studies have supported an association between serum galectin‐3 levels and atrial fibrosis demonstrated with delayed‐ enhancement magnetic resonance imaging in AF patients …”
Section: Introductionmentioning
confidence: 99%
“…9 Galectin-3 is an α-galactoside-binding lectin that has been shown to mediate cell-to-cell and cell-to-extracellular matrix interactions and act as a novel chemoattractant for monocytes and macrophages. 10,11 Studies have supported an association between serum galectin-3 levels and atrial fibrosis demonstrated with delayed-enhancement magnetic resonance imaging in AF patients. 12,13 In this study, we aimed to investigate the relation between serum galectin-3 levels and echocardiographic markers of thromboembolism, including LAAFV, LA/LAA-located SEC and thrombus.…”
mentioning
confidence: 95%